Mucosal immunity, respiratory illness and competitive performance in elite swimmers - Pyne, D. B.; McDonald, W. A.; Gleeson, M.; Flanagan, A.; Clancy, R. L.; Fricker, P. A. (Medicine & Science in Sports & Exercise, 2001)
Referat siehe MF 176053